Behavioral Response Study on Seismic Airgun and Vessel Exposures in Narwhals - Heide-Jørgensen, Mads Peter; Blackwell, Susanna B.; Tervo, Outi M.; Samson, Adeline L.; Garde, Eva; Hansen, Rikke G.; Ngô, Manh Cu’ò’ng; Conrad, Alexander S.; Trinhammer, Per; Schmidt, Hans C.; Sinding, Mikkel-Holger S.; Williams, Terrie M.; et al. (Frontiers in Marine Science, 2021)
One of the last pristine marine soundscapes, the Arctic, is exposed to increasing anthropogenic activities due to climate-induced decrease in sea ice coverage. In this study, we combined movement and behavioral data from animal-borne tags in a controlled sound exposure study to describe the reactions of narwhals, Monodon monoceros, to airgun pulses and ship noise. Sixteen narwhals were live captured and instrumented with satellite tags and Acousonde acoustic-behavioral recorders, and 11 of them were exposed to airgun pulses and vessel sounds. The sound exposure levels (SELs) of pulses from a small airgun (3.4 L) used in 2017 and a larger one (17.0 L) used in 2018 were measured using drifting recorders. The experiment was divided into trials with airgun and ship-noise exposure, intertrials with only ship-noise, and pre- and postexposure periods. Both trials and intertrials lasted ∼4 h on average per individual. Depending on the location of the whales, the number of separate exposures ranged between one and eight trials or intertrials. Received pulse SELs dropped below 130 dB re 1 μPa2 s by 2.5 km for the small airgun and 4–9 km for the larger airgun, and background noise levels were reached at distances of ∼3 and 8–10.5 km, respectively, for the small and big airguns. Avoidance reactions of the whales could be detected at distances >5 km in 2017 and >11 km in 2018 when in line of sight of the seismic vessel. Meanwhile, a ∼30% increase in horizontal travel speed could be detected up to 2 h before the seismic vessel was in line of sight. Applying line of sight as the criterion for exposure thus excludes some potential pre-response effects, and our estimates of effects must therefore be considered conservative. The whales reacted by changing their swimming speed and direction at distances between 5 and 24 km depending on topographical surroundings where the exposure occurred. The propensity of the whales to move towards the shore increased with increasing exposure (i.e., shorter distance to vessels) and was highest with the large airgun used in 2018, where the whales moved towards the shore at distances of 10–15 km. No long-term effects of the response study could be detected.